Спікання при високому тиску порошків сBN з добавками TіB₂ і Al та властивості одержаних полікристалів - Гарбуз, Т.О.; Беженар, Н.П.; Божко, С.А.; Белявина, Н.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The experimental samples of superhard polycrystals was received in cBN– TiВ₂–Al system
by sintering powders at high pressure and temperature (7,7 GPa, 2300 K). Influence of TiВ₂ quantity on structure, hardness, density, abrasive wear of the received polycrystals is studied.